WELDING OF MOBILE PLATFORM ELEMENTS MADE FROM MIXED GRADES OF HIGH-STRENGTH STEELS - Bożena SZCZUCKA-LASOTA; Tomasz WĘGRZYN; Bogusław ŁAZARZ; Krzysztof LUKASZKOWICZ; Adam JUREK; Krzysztof Ireneusz WILCZYŃSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2020)
In the mobile platform structure, there is an increasing necessity to weld steels from the various groups. For instance, it has become necessary to connect AHSS (Advanced High-Strength Steel) with fine-grained steels. This article verifies the possibility of obtaining accurate mixed welded joints from different grades of DOCOL 1400 steel (from the AHSS group) with S700 MC steel (from the fine-grained steel group). The structure, quality and mechanical properties of the obtained welded joints were thoroughly analysed. The joints were made at various welding speed with preheating to 80°C and without preheating.